Pengaruh Motivasi Kerja dan Sarana Prasarana Terhadap Kinerja Guru Di SMP Negeri Se-Kecamatan Mesuji Jaya - Risa Dwi Ayulia; Nur Ahyani; Darwin Effendi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study was conducted to address the problem of suboptimal teacher performance, which is assumed to be influenced by work motivation and the availability and utilisation of facilities and infrastructure in public junior high schools in Mesuji Raya District. The research aims to describe and analyse: (1) the effect of work motivation on teacher performance, (2) the effect of facilities and infrastructure on teacher performance, and (3) the combined effect of work motivation and facilities and infrastructure on teacher performance in these schools. A quantitative approach with a correlational research design was employed. The population consisted of all teachers in public junior high schools across Mesuji Raya District, and a sample of 90 teachers from nine schools was selected using the Slovin formula. Data were collected through questionnaires and documentation, developed based on indicators of work motivation, facilities and infrastructure, and teacher performance, and tested for validity and reliability. Data were analysed using correlation and multiple regression techniques with the assistance of SPSS version 26, preceded by prerequisite tests including normality, linearity, and multicollinearity tests. The findings indicate that: (1) work motivation has a significant effect on teacher performance, (2) facilities and infrastructure have a significant effect on teacher performance, and (3) work motivation and facilities and infrastructure jointly have a significant effect on teacher performance in public junior high schools in Mesuji Raya District, contributing 72.8%, while the remaining 27.2% is influenced by other factors not examined in this study.